Semiotic analysis of graffiti discourse In light of the methodology of Roland Barthes and Charles Peirce (Al-Academy, 2024)
Graffiti is an art that refers to pictures and words painted on the walls of buildings, usually using spray colors, It is used as a form of protest and rebellion, although this art is deeply rooted in history since the first time man painted on the walls of caves, it has gone through stages that changed its form, reasons, and purpose, among the historical stages in the world are the stage of the French Revolution, the stage before the Internet, then the stage of the era of globalization, the small village, the spread of social networking sites, and the excessive use of electronic sites. Although this art was more conservative during the French Revolution, we find that it later turned into street culture and became an illegal act. It is rejected by societal norms and is sometimes described as a cancer to societies and appears as a cracked house next door, distorting the view. Or perhaps it is simply that its perpetrator is another victim of social alienation. Placing paint on walls is still punishable by imprisonment and large amounts of fines, With the introduction and spread of new digital media in the practice of expressing graffiti at the present time, the rules of the game have changed, improving the quality of graffiti, establishing social links, and disseminating messages on a wider and faster scale than before. Thus, the new media represented by various means of communication are today working to intensify democracy in the communities of graffiti artists through learning for wide groups of artists and, most importantly, the feeling of “community,” that is, “the direct physical social interaction provided by the community.” This is an additional advantage that it has gained. These modern technologies put it in an advanced position compared to graffiti works in public squares. In this research, in order to develop a methodology for analyzing graffiti discourse through critical discourse analysis through a combined approach between detailed descriptive analysis, textual manifestations, analysis of arguments, and methods of proof, we adopted the method of semiotic analysis of graffiti discourse, and through the use of two semiotic approaches by well-known thinkers, the French philosopher Roland Barthes. Barthes 1915-1980 AD) and the American thinker (Charles Sanders Peirce 1839-1914 AD).